Determinan Kemiskinan di Wilayah Metropolitan “Kedungsepur” Jawa Tengah - Viarum, Arthanti; Susilowati, Dwi (Fakultas Ekonomi Universitas Samudra, 2024)
The study aims to examine the influence of several economic factors on poverty levels in the Kedungsepur metropolitan area. Factors analyzed include the unemployment rate, average years of schooling, and per capita expenditure. By using E-Views 9 software to process statistical data, panel data regression analysis has been carried out with the preferred common effect model. The results show that both the unemployment rate and the average number of years of schooling have a positive relationship with the poverty rate in Kedungsepur. On the other hand, per capita expenditure has a negative effect on poverty levels. These findings indicate that local governments need to focus more efforts on increasing access to quality education and increasing people's purchasing power to effectively reduce poverty in the region.